2010
DOI: 10.1021/jp107823s
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Theoretical Study of the Zero-Field Splitting in Coordination Complexes of Mn(III). Density Functional Theory versus Multireference Wave Function Approaches

Abstract: This paper presents a detailed evaluation of the performance of density functional theory (DFT) as well as complete active space self-consistent field (CASSCF)-based methods (CASSCF and second-order N-electron valence state perturbation theory, NEVPT2) to predict the zero-field splitting (zfs) parameters for a series of coordination complexes containing the Mn(III) ion. The physical origin of the experimentally determined zfs's was investigated by studying the different contributions to these parameters. To th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
150
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(168 citation statements)
references
References 83 publications
18
150
0
Order By: Relevance
“…Similar conclusions for other Mn(III) systems were reached in other papers from Neese's group. 26,79,80 Moreover, some model Mn(III) complexes were the topic of an ab initio study by Maurice et al 81,82 The conclusion of this discussion might be that the difficult systems, with spatially nearly degenerate states, require the use of the most advanced theoretical tools, such as the NEVPT2/QDPT combination. What is surprising, to a certain extent, is the fact that our calculations for the apparently "easy" case of nickel(II), with the triplet ground state quite far below the excited states, show the same trend as the "difficult" ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions for other Mn(III) systems were reached in other papers from Neese's group. 26,79,80 Moreover, some model Mn(III) complexes were the topic of an ab initio study by Maurice et al 81,82 The conclusion of this discussion might be that the difficult systems, with spatially nearly degenerate states, require the use of the most advanced theoretical tools, such as the NEVPT2/QDPT combination. What is surprising, to a certain extent, is the fact that our calculations for the apparently "easy" case of nickel(II), with the triplet ground state quite far below the excited states, show the same trend as the "difficult" ions.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 We also reported a combination of molecular dynamics (MD) simulations and ZFS calculations yielding a time correlation function for the fluctuations of the ZFS in aqueous nickel(II) solution. 15,16 The development of the theoretical tools to calculate the ZFS parameters by quantum chemistry technique over the last decade has been quite impressive, with Frank Neese and his group as the leading team, 10,11,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] but also with important contributions from other authors. [31][32][33][34][35][36][37] The development has followed two routes, making use of either efficient density functional theory (DFT) techniques or of high-end wavefunction methods based on multi-configurational SCF techniques (such as complete active space self-consistent field (CASSCF) and related extensions).…”
Section: Introductionmentioning
confidence: 99%
“…Based on qualitative reasoning, the barrier was identified with 2 DS where D is the axial zero-field splitting (ZFS) parameter of the investigated multiplet (also called the 'magnetic anisotropy'). In Mn12, a net D -value of only -0.46 cm -1 arises, mainly from the coupling of the local D -values of the Mn III ions, which typically display local D -values of around≈-2 cm -1 [12]. Based on this model it was concluded that in order to obtain SMMs with higher blocking temperature, it is necessary to synthesize molecules that have a large and negative D -value and a large total spin S .…”
Section: Page 5 Of 143mentioning
confidence: 99%
“…The negative D -value is necessary in order to ensure that the magnetic sublevels with the largest magnetic moments are lowest in energy and hence that the system shows a large net magnetization, while the large spin S would ensure a high barrier. A large total spin S (beyond 5/2 S = for d-elements and [16], iron [Fe 8 O 2 (OH) 12 (L) 6 ] 8+ [17] and a Mn 6 SMM, [Mn III 6 (μ 3 -O) 2 (μ 3 -ONR) 2 (μ 2 -ONR) 4 ] 2+ (reported record barrier -1 57.6 cm U = , 4 B T K ∼ [18]). Systems with up to the impressive total spin of 83/2 S = have been reported [19].…”
Section: Page 5 Of 143mentioning
confidence: 99%
“…A deeper understanding of the microscopic processes related to magnetic interactions has been a very interesting topic in computational chemistry since the first half of the twentieth century [1][2][3][4][5][6][7][8][9][10]. The idea of using molecules, rather than the ionic and metallic lattices of typical magnets, stems from the rapid development of functional molecular materials, and gives a better insight into the nature of coupling between paramagnetic centers.…”
Section: Introductionmentioning
confidence: 99%